SPTBN5, Encoding the βV-Spectrin Protein, Leads to a Syndrome of Intellectual Disability, Developmental Delay, and Seizures - Khan, Amjad; Bruno, Lucia Pia; Alomar, Fadhel; Umair, Muhammad; Pinto, Anna Maria; Khan, Abid Ali; Khan, Alamzeb; Saima; Fabbiani, Alessandra; Zguro, Kristina; Furini, Simone; Mencarelli, Maria Antonietta; et al. (Frontiers in Molecular Neuroscience, 2022)
Whole exome sequencing has provided significant opportunities to discover novel candidate genes for intellectual disability and autism spectrum disorders. Variants in the spectrin genes SPTAN1, SPTBN1, SPTBN2, and SPTBN4 have been associated with neurological disorders; however, SPTBN5 gene-variants have not been associated with any human disorder. This is the first report that associates SPTBN5 gene variants (ENSG00000137877: c.266A>C; p.His89Pro, c.9784G>A; p.Glu3262Lys, c.933C>G; p.Tyr311Ter, and c.8809A>T; p.Asn2937Tyr) causing neurodevelopmental phenotypes in four different families. The SPTBN5-associated clinical traits in our patients include intellectual disability (mild to severe), aggressive tendencies, accompanied by variable features such as craniofacial and physical dysmorphisms, autistic behavior, and gastroesophageal reflux. We also provide a review of the existing literature related to other spectrin genes, which highlights clinical features partially overlapping with SPTBN5.